Epidemiology of venous thromboembolism in people with active tuberculosis: a systematic review and meta-analysis protocol. Issue 11 (12th November 2019) - Awana, Philippe Armel; Danwang, Celestin; Tochie, Joel Noutakdie; Bigna, Jean Joel
Abstract : Introduction: In recent years, a hypothesis has been raised that people with tuberculosis are at risk for developing venous thromboembolism (VTE). However, much remains to be understood about the interplay between VTE and tuberculosis. Therefore, through a global systematic review and meta-analysis, the current study aims at investigating the association between exposure to active tuberculosis and risk of VTE, and determining the prevalence and incidence of VTE in people with active tuberculosis. Methods and design: We will include cohort studies, case–control and cross-sectional studies performed among adults (>15 years) with active tuberculosis. EMBASE, Medline, Global Index Medicus and Web of Knowledge will be searched for relevant records published until 31 August 2019, without any language restriction. The review will be reported according to the Meta-analysis Of Observational Studies in Epidemiology guidelines. After screening of titles and abstracts, study selection, data extraction and risk of bias assessment; we shall assess the studies individually for clinical and statistical heterogeneity. Random-effect meta-analysis will be used to pool studies judged to be clinically homogenous. The Egger's test and visual inspection of funnel plots will be used to assess publication bias. Results will be presented by country and region. Ethics and dissemination: Since primary data are not collected in this study, ethical approval is not required. This review is expected to provide relevant data on the epidemiology of VTE in people with tuberculosis. The final report will be published in a peer-reviewed journal. PROSPERO registration number: CRD42019130347.